LE LE DEVELOPPEMENT DU MÉDIA DE LA BANDE DESSINÉE NUMÉRIQUE POUR LA COMPÉTENCE DE LA COMPRÉHENSION ÉCRITE DU FRANÇAIS SUR LES HOBBIES OU LES GOÛTS UTILISANT MACROMEDIA FLASH - Ranuta, Juniaga; Handayani, Sri; Agustiningrum, Tri Eko (Didacticofrancia: Journal Didactique du FLE, 2016)
Media as teacher’s support is very helpful to reach the purpose of learning. One of media thatcan be used in french language learning is digital comic. Digital comic or e-comic is a transformation of media technologies that began in the form of print out into digital with the eletronicformat. This research used a Research and Development (R&D) method. According to Sugiyono (2010: 409-427), there are ten steps of the research, but this research is only use five steps,that are formulating potential and problems, collecting the data, making the product design,validating design and design revision.The result of this research is a digital comic media basedof macromedia flash application for reading skill with the theme les hobbies ou les goûts. Thismedia includes two based subjects which in the syllabus curriculum 2006, namely dire ce quel’on aime and dire ce que l’on n’aime pas. Then, in the last step, that media is consulted toFrench expert to revise. After revision from expert’s advice, the media is being validated by theexperts and can be used by teachers in their experiences in the classroom.